Expansions-1

From Homeworkwiki

Jump to: navigation, search

Evaluate :

(i) (a + 2b) 2 (ii) (2a - 3b) 2 (iii) (2a + 3b - 4c) 2

Solution:

(i) (a + 2b) 2 = (a) 2 + 2 X a X 2b + (2b) 2

= a 2 + 4 a b + 4 b 2

(ii)(2a - 3b) 2 = (2a) 2 - 2 X 2a X 3b + (3b) 2

= 4 a 2 - 12 a b + 9 b 2

(iii) (2a + 3b - 4c) 2 = (2 a ) 2 + (3 b) 2 + ( - 4c) 2 + 2 X 2a X 3b + 2 X 3b X ( - 4c) + 2 X ( - 4c) X (2a)

= 4 a 2 + 9 b 2 + 16 c 2 + 12 a b - 24 b c - 16 c a

Personal tools
McAfee SECURE sites help keep you safe from identity theft, credit card fraud, spyware, spam, viruses and online scams